The rat mammary gland undergoes dynamic transcriptomic and lipidomic modifications from pre-puberty to adulthood - David Tovar-Parra; Alec McDermott; Melany N. Juarez; Jysiane Cardot; Mame Sokhna Sylla; Line Berthiaume; Géraldine Delbès; Martin Pelletier; Étienne Audet-Walsh; Isabelle Plante (Scientific Reports)
Abstract Mammary gland development is a complex process involving dynamic interaction between the epithelial and stromal components at different critical stages, particularly around puberty. While epithelial tissue changes are well-documented, stromal mechanisms are less understood. To address this gap, this study employed histology, lipidomic, and transcriptomic analyses to investigate molecular and cellular dynamics in the mammary gland during pre-puberty (Post Natal Day (PND21)), peri-puberty (PND46), and adulthood (PND90) in rats. The epithelial area was significantly smaller at PND21 than at PND46 and PND90, with a higher complexity at PND21 compared to PND46. Significant differences in adipocyte number and size were observed between PND21, PND46, and PND90. Transcriptomic analysis revealed that 1563 genes changed significantly between PND21 and PND46, with only 14 genes altered between PND46 and PND90. Enrichment analyses indicated dynamic regulation of pathways related to proliferation, differentiation, lipid metabolism, and immune responses. In lipidomic analysis, 29/43 and 7/43 fatty acids differed significantly between PND21 - PND46 and PND46 - PND90, respectively. These results suggest that mammary gland development involves complex interactions between metabolic demands, hormonal regulation, and immune responses.